MLST genotypes and antibiotic resistance of Campylobacter spp. isolated from poultry in Grenada. - Stone, Diana; Davis, Margaret; Baker, Katherine; Besser, Tom; Roopnarine, Rohini; Sharma, Ravindra (BioMed Research International, 2013)
This study determined whether multilocus sequence types (MLST) of Campylobacter from poultry in 2 farms in Grenada, West Indies, differed by farm, antimicrobial resistance and farm antibiotic use. Farm A used fluoroquinolones in the water and Farm B used tetracyclines. The E-test was used to determine resistance of isolates to seven antibiotics. PCR of the IpxA gene confirmed species and MLST was used to characterize 38 isolates. All isolates were either C. jejuni or C. coli. Farm antibiotic use directly correlated with antimicrobial resistance of Campylobacter isolates. Almost 80% of the isolates from Farm A were fluoroquinolone resistant and 17.9% of the isolates from Farm B were fluoroquinolone resistant. All Campylobacter isolates from Farm A were tetracycline sensitive, whereas 35.7% of isolates from Farm B were tetracycline resistant. Six previously recognized sequence types (STs) and 2 novel STs were identified. Previously recognized STs were those overwhelmingly reported from poultry and humans globally. Isolates with the same ST did not always have the same antibiotic resistance profile. There was little ST overlap between the farms suggesting that within-farm transmission of Campylobacter genotypes may dominate. MLST typing was useful for tracking Campylobacter spp. among poultry units and can help elucidate Campylobacter host-species population structure and its relevance to human health.